ORNAC in a Nutshell - Farley, Margaret (Operating Room Nurses Association of Canada Journal, 2001)
We bid farewell to Executive member Shelly Zareski, Treasurer. Shelly started as a representative of Nova Scotia in Banff in 1991, so it seems fitting that she leaves from the same venue. We also bid farewell to Past President Donna Farid. Rumor has it that Donna was a Board member in 1991 as well. We thank both of these dedicated ladies for their contributions over the years.